Analisis Tingkat Penggunaan Aplikasi MiChat Sebagai Sarana Media Bisnis Prostitusi Online Menggunakan Metode TAM - Andika Agus Yudhistira; Joy Nashar Utama Jaya (STMIK Budi Darma, 2022)
The development of Information and Communication Technology has had a great impact on human life, with these technological advances, it has changed the way large and small-scale business actors turn to businesses that are considered haram, namely online prostitution. Social media as one of the technological developments has provided GPS features that can make it easier for users to find other users around, one of which is the MiChat application. This application is one of the applications that is misused as a means of online prostitution business media in various regions and one of them is North Penajam Paser Regency. This study aims to identify and describe the business processes used in the MiChat application, and the misuse of MiChat as a means of online prostitution. This study uses the TAM (Technology Acceptance Model) method. The sources of data used are primary and secondary data obtained from respondents and the study of literature which is the author's reference